Hubungan Kepuasan Kerja dengan Loyalitas Perawat di Rumah Sakit (Literature Review) - Veronica, Rina (STIKes Persada Husada Indonesia, 2024)
One might view loyalty as fidelity or obedience. There is an emotional component to loyalty. There are many variables that can influence a person's ability to develop a loyal attitude. One of the factors causing decreased employee loyalty is job satisfaction. A person's feelings towards their work are called job satisfaction. The aim of this literature study is to ascertain how nurse loyalty and job satisfaction relate to each other in the hospital environment. The process involves using Science Direct, PubMed, Proquest, Google Scholar, and other electronic databases to search. Journal publications in 2019–2024 (less than 5 years) and national and international publications discussing the relationship between nurse loyalty and job satisfaction were inclusion criteria in the literature evaluation process. The results of the review show that there is a relationship between job satisfaction and nurse loyalty in hospitals.